Postmemory Analysis In Jacqueline Woodson’s Brown Girl Dreaming - Nur Khafifah M; Aprinus Salam (Universitas Cokroaminoto Palopo, 2026)
This study explores the representation of transgenerational trauma in Brown Girl Dreaming (2014) by Jacqueline Woodson through the theoretical lens of postmemory as developed by Marianne Hirsch. Postmemory, originally formulated in the context of Holocaust studies, refers to the affective and symbolic inheritance of trauma by generations who did not directly experience the original events. This research argues that Brown Girl Dreaming, although presented as a poetic memoir of a Black girl's childhood, serves as a complex narrative space in which the legacy of slavery, racial segregation, and structural injustice is mediated and internalized across generations. The study employs a qualitative literary analysis method using close reading as the major tool to identify three key mechanisms of postmemory in the text: familial transmission, embodied memory, and narrative fragmentation. These mechanisms reveal how collective trauma is not only preserved in language and story but also in gestures, silences, and poetic form. Furthermore, this research investigates how Woodson constructs her identity through the internalization of inherited loss and imaginative identification, demonstrating how a post-traumatic subject can move from a position of passive inheritance to active narrative agency. By applying the postmemory framework to an African-American children’s memoir, this research contributes to the growing field of memory studies in the scope of postmemory theory beyond Eurocentric contexts. It also opens new directions for the analysis of Black diasporic and children’s literature. Significantly, the findings demonstrate that children’s literature is not merely a didactic or developmental genre, but a powerful medium through which intergenerational trauma can be reimagined and critically engaged. Brown Girl Dreaming exemplifies how children’s narratives can carry the weight of historical memory while cultivating critical consciousness in both young and adult readers.